2003
DOI: 10.1590/s1677-04202003000300004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead on the phytochemistry of Tithonia diversifolia exposed to roadside automotive pollution or grown in pots of Pb-supplemented soil

Abstract: Tithonia diversifolia, a ruderal weedy species utilized in agroforestry, is widely distributed in the tropics, often being found in wasteland, margins of polluted city rivers and roadsides. The objective of this study was to compare plants sampled at a light and heavy traffic roadside for metal concentration and foliar compounds which may be related to senescence and/or detoxification of metals. The field survey was followed by an experiment in pots of Pb-acetate-supplemented soil to verify if the same respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
4
10
0
5
Order By: Relevance
“…According to Singh et al (2006) the enhancement in carotenoid level in heavy metals-treated plants is probably a part of strategy adopted by the plant to counteract the toxic effect of free radicals generated under heavy metal toxicity. On the other hand, chlorophyll concentration was not affected in any Pb treatments corroborating with results presented by Olivares (2003) in Tithonia diversifolia exposed to Pb through the roadside automotive pollution. One of the most important enzymes involved in the chlorophyll biosynthesis is the aminolevulinate dehydratase (ALA-D) that, in the present study, had its activity reduced only at the highest Pb concentration when compared with the control.…”
Section: Discussionsupporting
confidence: 89%
“…According to Singh et al (2006) the enhancement in carotenoid level in heavy metals-treated plants is probably a part of strategy adopted by the plant to counteract the toxic effect of free radicals generated under heavy metal toxicity. On the other hand, chlorophyll concentration was not affected in any Pb treatments corroborating with results presented by Olivares (2003) in Tithonia diversifolia exposed to Pb through the roadside automotive pollution. One of the most important enzymes involved in the chlorophyll biosynthesis is the aminolevulinate dehydratase (ALA-D) that, in the present study, had its activity reduced only at the highest Pb concentration when compared with the control.…”
Section: Discussionsupporting
confidence: 89%
“…This situation was confirmed by the opinion of Olivares (2003), which statedd that the tendency of a decrease in chlorophyll content was in line with the increase of Pb. There was a link between the concentration of Pb with the changes in total chlorophyll content in the leaves.…”
Section: Content Of Chlorophyllsupporting
confidence: 53%
“…Interestingly, in M plants under low P, Cd addition affected foliar APase activity, resulting in an increase in relation to non Cdtreated plants. Increases in APase activity were observed in radish (Raphanus sativus) leaves submitted to excessive amounts of Cr (Dube et al, 2004) and in Mexican sunflower (Tithonia diversifolia) plants under excess Pb (Olivares, 2003). Hence, it is suggested that Cd may be interfering in P uptake and inducing APase activity to counteract a possible extra demand for P in the intracellular environment by forming a non-toxic metal complex with P compounds.…”
Section: Mycorrhiza Influence On Maize Under Cadmium Stressmentioning
confidence: 99%